(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The aim of the study was to determine the effectiveness of organic and intensive watermelon cultivation technologies under the conditions of the Steppe zone of Ukraine. Field experiments were conducted on low-humus ordinary chernozem at the “Shchedryi Lan” farming enterprise in the Kramatorsk district of Donetsk region. The study evaluated the efficiency of implementing organic technology (application of poultry manure at 20 t/ha + incorporation of post-harvest green manure + foliar feeding with HelpRost Vegetable and HelpRost Boron + spraying with biopreparations Mycohelp and Actoverm) and intensive technology (N48P144K144 + foliar feeding with Avangard Vegetable and Avangard Boron + treatment with Uniform and Transform preparations). It was established that under the Steppe conditions of Ukraine, the initial growth stages of watermelon plants under organic technology proceeded more slowly compared to the intensive system (by 1–5 days), while technical maturity occurred 9 days earlier. Under the intensive cultivation system, plants exhibited the highest biometric parameters: main shoot length reached 118.5 cm, the number of lateral shoots was 6.8 per plant with a total length of 835 cm, the number of leaves was 69.5 per plant, and the number of fruits was 3.5 per plant. The organic cultivation system was significantly inferior in all biometric indicators. The application of intensive technology ensured the highest watermelon yield, averaging 83.3 t/ha over the years of study. Increasing the efficiency of organic approaches is possible only through the enhancement of cultivation technologies by additional applications of biopreparations aimed at optimizing plant nutrition.